The chemistry of oils and fats : sources, composition, properties and uses. - Gunstone, Frank Denby, 1923-2021 (Oxford : Blackwell, 2004)
The three major macronutrients are proteins, carbohydrates, and lipids (oils and fats). This book is devoted to lipids, which are an important part of life for all of us. What are these materials in molecular terms? Where do they come from? What happens to them between the harvesting of crops and the appearance of the oils and fats in different products in the supermarket? How does nature produce these molecules and can we act on nature to modify the materials to increase their beneficial properties? How important are the minor products present in the fats that we consume? Since oils and fats vary, how can we analyse them? What are their physical, chemical and nutritional properties? How do the fats that we consume affect our health and well-being in both quantitative and qualitative terms? What are their major food and non-food uses? This book provides a broad source of reference on oils and fats chemistry for graduates entering the food and oleochemical industries, postgraduate researchers and nutritionists. It offers a point of entry to the detailed literature.
Keywords: Olie; Vetten